Review of migraine incidence and management in obstetrics and gynaecology. (September 2019) - Tanos, Vasilios; Raad, Elissa Abi; Berry, Kelsey Elizabeth; Toney, Zara Abigail
Abstract: Purpose: Migraines are the third most prevalent disorder, and seventh-highest specific cause of disability worldwide. Migraines have a multitude of underlying aetiologies; the pathology may come as a result of hormonal treatment or as a sole symptom during menstrual cycle or pregnancy, with variable intensity and duration. In addition, clinicians should be fully aware of the potential complications and well-versed in management options. Methods: A systematic review of the incidence, symptoms, treatment options and complications among women suffering from migraines in gynaecology, as well as obstetrical cases has been performed. The significance of migraines as a marker in antenatal care and contraception treatment has also been investigated. Results: The incidence of migraines in gynaecological and obstetrical cases, and contraceptive users were 11.7–12.5 %, 9–38.5 %, and 16.7–54.7% respectively. There is an average six-fold increase in the risk of stroke in women who take combined hormonal contraception and suffer from migraines. Four papers with 1565 patients proposed the combination of triptans along with the progesterone only pill. Desogestrel 75mcg/day was found to reduce the intensity of migraines compared to the combined hormonal contraceptives. The risk of gestational hypertension, pre-eclampsia, low birth weight, and preterm birth was found to be increased in pregnant women suffering from migraines. Conclusion: Migraines have a high incidence in gynaecology and obstetrics. Health care providers must include screening questions when history taking to identify women with migraines and effectively manage them. Proper follow-up and treatment is required for all women with migraines in order to minimize the risk of cerebrovascular events, and negative pregnancy outcomes. Women with migraines are advised to avoid combined hormonal contraception and use progesterone only pills.